Optimal Dynamic Coordination of V2G and Fuel Cells as Frequency Control Ancillary Services - Pradana, Adlan; Astriani, Yuli; Haque, Md. Mejbaul; Nadarajah, Mithulananthan (Global Power, Energy and Communication Conference (Online), 2025)
The increasing penetration of renewable energy sources in modern power grids introduces significant challenges in maintaining frequency stability due to the intermittent nature of these resources. This study investigates the dynamic coordination of Vehicle-to-Grid (V2G) systems and fuel cells as Frequency Control Ancillary Services (FCAS) to enhance grid stability during disturbances. A simulation model incorporating V2G systems, fuel cells, and conventional power plants was developed to evaluate their combined response to frequency deviations. The coordination framework leverages optimized proportional-integral-derivative (PID) controllers for each system component, ensuring effective frequency stabilization while adhering to operational constraints such as ramp rates, state of charge for batteries, and hydrogen storage levels for fuel cells. The results demonstrate that the fast response of V2G systems complements the sustained power output of fuel cells, significantly improving the overall frequency response. This study highlights the potential of integrating V2G and fuel cells into FCAS strategies, paving the way for a resilient and low-carbon grid.